Manufacturing Technology Status and Developmental Trend for Spiral Bevel Gear Used in Automotive Drive Axle - Deng Xiaozhong; Deng Jing; Xie Junjun; Nie Shaowu (Jixie chuandong)
The manufacturing status and existing problems of spiral bevel gears used in automotive drive axle of China is analyzed.As one of the largest manufacturing and consuming countries for such gears,manufacturing industry of spiral bevel gears in China is faced with the difficulties of poor production ability for high-level products,as well as low profit for mid-level and low-level products.Taking current manufacturing technologies and processes into consideration,the developmental trend of manufacturing processes suitable for domestic industry is analyzed and summarized from the following three aspects,detailed design of adjusting parameters,network-based closed loop manufacturing technology and near / net shaped precision forging,which would be the prospect for national manufacturing industry of spiral bevel gears used in automotive drive axle.